Black women's health in nursing teaching (Research, Society and Development, 2021)
This study aims to explore the inclusion of health promotion for black women in the curricula of different nursing courses in the State of Bahia. In order to achieve the proposed objective, an exploratory documentary research was used as a methodological path, which used the IBGE, e-MEC, SciELO, LILACS, Academic Google, BVS and official HEI portals as a database to analyze the curriculum and the pedagogical projects of the courses. 14 available PPC were analyzed, leaving only 06 institutions that presented subjects with themes focused on ethnic issues and health promotion for black women in the menus. It is concluded that there is a scarcity regarding the ethnic-racial subjects involved in the process of training future graduates, unsatisfactorily generating the teaching of health promotion for black women.